The Effectiveness of Role Playing Model as a Learning Strategy in Improving Students' Storytelling Skills: A Classroom Action Research Study - Parida Yuli Yanti; Rahmat Kartolo; Sutikno (PT Inovasi Pratama Internasional, 2026)
The problem underlying this research is the low storytelling skills of students, as seen from the results of daily tests which show that only 5 out of 25 students (16.6%) achieved scores above the Minimum Completion Criteria (KKM) of 70. The learning model used previously tended to be conventional and did not involve students actively. This research is a Classroom Action Research (CAR) which is carried out in two cycles. Data were collected through observation of teacher and student activities and storytelling skills tests (pretest and posttest). In cycle I, the average pretest score of students was 64.8 with only 2 students (8%) completing the task. After learning using the role-playing model, the posttest results showed an increase: 12 students (48%) completed the task and 13 students (52%) had not completed the task, which means there was a 40% increase in completion compared to the initial conditions. In cycle II, there was a more significant increase. Of the 30 students, 21 students (70%) achieved completion, and 9 students (30%) had not completed the task. Overall, the increase in completion from pre-action to cycle II was 61.4% (from 8% to 70%). Meanwhile, the average teacher activity increased from 79% in cycle I to 84% in cycle II, indicating an increase of 5%. This increase was influenced by the teacher's efforts to improve learning strategies by encouraging students to be active, confident, and creative in storytelling. The results of the study showed that the application of the role-playing model was able to significantly improve students' storytelling skills. This method provides an active, enjoyable learning experience and encourages full student participation, both as players and spectators who actively provide responses. Thus, the role-playing model is effectively used as a learning strategy in improving elementary school students' storytelling skills, especially in learning Indonesian